Second Harmonic Generation of 266 nm Laser Beam Using BBO Nonlinear Crystal - Khorsheed, Suha Mousa; Al-Obaidi, Raneen Salam (Iraqi Journal of Science, 2021)
Second harmonic generation (SHG) is a phenomenon observed in nonlinear optics that leads to frequency duplication for a high intensity laser incident on nonlinear crystal using BBO crystal. The SHG yield is achieved when the photons interact with a nonlinear optical material and effectively combine to form new photons with double frequency, and therefore double energy and half wavelength. This paper is concerned with the establishment of an SHG experiment to govern the process of producing half-wavelength laser beam from the input one. The theoretical effort was extended to compute the efficiency by using MATLAB software based on mathematical relationships. The values of the conversion maximum efficiencies, which were computed as a function of the input and output powers of the theoretical computations, were 15.6% and 16% at input and output power values of 0.6 and 0.1, respectively. The experimental results of the laser source of 532nm wavelength (fundamental frequency was 0.563x1015s-1) gave a half wavelength of 266nm (double frequency was 1.126x1015s-1). The conversion efficiencies, computed as a function of the input and output powers of the experimental measurements, were 14.32% and 12.97%, respectively.